THU0675 Development and psychometric validation of a tool to assess the fears of patients with chronic inflammatory rheumatic diseases: the fair scale. (15th June 2017) - Gossec, L; Chauvin, P; Hudry, C; Cukierman, G; Saulot, V; Russo-Marie, F; Chalus, T de; Joubert, JM; Saraux, A; Berenbaum, F
Abstract : Background: Patients (pts) with chronic inflammatory rheumatic diseases (CIRDs) such as rheumatoid arthritis (RA) and axial spondyloarthritis (axSpA) have fears related to their disease that can negatively impact health-related quality of life and compromise treatment adherence. Objectives: To develop and validate a patient-reported outcome (PRO) questionnaire to explore fears related to CIRDs using the Fears Assessment in Inflammatory Rheumatic Diseases (FAIR) Scale. Methods: The preliminary questionnaire included 44 items (23 related to fears) most frequently cited by pts in a qualitative study of 50 French pts. 1 Each item was formulated as an affirmative sentence and scored from 0 (completely disagree) to 10 (totally agree). Item scores were summed to provide a total score. The questionnaire was finalised and validated. Pts diagnosed with RA (EULAR/ACR criteria) or axSpA (ASAS criteria), recruited during routine visits by 100 participating rheumatologists across France, completed the preliminary questionnaire, HAD (Hospital Anxiety and Depression) and AHI (Arthritis Helplessness Index) scores. Redundant items (inter-item correlation coefficient >0.65) were eliminated. For the others, internal consistency (Cronbach alpha) and the factorial structure of the scale (principal component analysis) were assessed. Pts were classified according to their level of fears (cluster analysis) and corresponding score thresholds were determined (ROC analysis). The final questionnaire was independently translated into English and back into French twice, with reconciliation of the translated texts. Results: 672 pts were included: 432 RA pts (mean±SD disease duration was 13.1±11.4 years, DAS28[ESR] was 2.6±1.2, 77.3% were taking biologics) and 240 axSpA pts (disease duration was 13.8±10.6 years, BASDAI was 3.3±2.2, 72.7% were taking biologics). The final FAIR Scale included 10 questions (Table) with total scores ranging 0–100. Mean±SD scores were 51.2±25.4 in RA and 60.5±22.9 in axSpA. Three pt groups were identified, characterised by high, moderate and low level of fears (17.2%, 41.1% and 41.7% of the population, respectively). The corresponding thresholds of the total score were 77 and 51, respectively. Fear scores were correlated with HAD scores for anxiety (r=0.47) and depression (r=0.40) and with the AHI (r=0.50). Conclusions: The FAIR Scale is a 10-question PRO to evaluate disease-related fears in CIRD pts. In this pt population, 17.2% had high fear scores, contrasting with a disease that is often well-controlled. The FAIR Scale was associated with psychological distress. This psychometrically-validated and easy to use questionnaire could be used to improve pt-physician dialogue in CIRDs and also be of value in clinical studies. Further validation in other populations is needed. References: Berenbaum F. PloS One 2014; 9(12):e114350. Acknowledgements: The authors acknowledge Costello Medical Consulting, funded by UCB Pharma, for editorial assistance. This study was funded by UCB Pharma and Arthritis Foundation Olivier Courtin. Disclosure of Interest: L. Gossec Grant/research support from: UCB Pharma, Lilly, Consultant for: AbbVie, BMS, Celgene, Janssen, Novartis, MSD, UCB, P. Chauvin: None declared, C. Hudry: None declared, G. Cukierman Employee of: UCB Pharma, V. Saulot: None declared, F. Russo-Marie: None declared, T. de Chalus Employee of: UCB Pharma, J. M. Joubert Employee of: UCB Pharma, A. Saraux Consultant for: UCB Pharma, F. Berenbaum: None declared